1996
DOI: 10.1093/glycob/6.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized low density lipoprotein stimulates aortic smooth muscle cell proliferation

Abstract: We have investigated the effects of oxidized low density lipoproteins (Ox-LDL) on aortic smooth muscle cell (SMC) proliferation and the biosynthesis of glycosphingolipids. We found that Ox-LDL exerted a concentration, time, and temperature dependent alteration of cell proliferation and the biosynthesis of lactosylceramide. At low concentrations (5-10 micrograms/ml medium) Ox-LDL stimulated cell proliferation measured by an increase in the incorporation of [3H]-thymidine in cells and the synthesis of lactosylce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…Because VEGF induced LacCer synthase activity, we first used D-PDMP, initially shown to be an inhibitor of GlcCer synthase 31 but later proven to be an inhibitor of purified LacCer synthase. 28,32 Our studies provided evidence that VEGF-induced LacCer/GlcCer synthesis, PECAM-1 gene/protein expression, and angiogenesis was inhibited by D-PDMP in a dose-dependent fashion. Moreover, this inhibitory effect was by passed by LacCer but not GlcCer, suggesting that VEGF targets the LacCer synthase to induce angiogenesis.…”
Section: Discussionmentioning
confidence: 75%
“…Because VEGF induced LacCer synthase activity, we first used D-PDMP, initially shown to be an inhibitor of GlcCer synthase 31 but later proven to be an inhibitor of purified LacCer synthase. 28,32 Our studies provided evidence that VEGF-induced LacCer/GlcCer synthesis, PECAM-1 gene/protein expression, and angiogenesis was inhibited by D-PDMP in a dose-dependent fashion. Moreover, this inhibitory effect was by passed by LacCer but not GlcCer, suggesting that VEGF targets the LacCer synthase to induce angiogenesis.…”
Section: Discussionmentioning
confidence: 75%
“…45 This appeared to be a specific effect of Ox-LDL, since Ox-LDL did not stimulate the activity of GlcT-1 and/or the activities of other relevant catabolic enzymes in GSL metabolism ( Figure 1). Preincubation of ASMCs with an antibody against either Ox-LDL or GalT-2 compromised Ox-LDL-mediated activation of GalT-2 and cell proliferation.…”
Section: Effect Of Ox-ldl On Galt-2 and Laccermentioning
confidence: 91%
“…Preincubation of ASMCs with an antibody against either Ox-LDL or GalT-2 compromised Ox-LDL-mediated activation of GalT-2 and cell proliferation. 45 Next, it was shown that LacCer itself markedly stimulated the proliferation of ASMCs. 46 To substantiate these studies further, we used an inhibitor D-threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (D-PDMP) (Figure 2).…”
Section: Effect Of Ox-ldl On Galt-2 and Laccermentioning
confidence: 99%
“…Studies by Chatterjee et al 18,19 have also shown that the biosynthesis of lactosylceramide from glucosylceramide is regulated by LDL and ox-LDL levels. Higher levels of LDL suppress lactosylceramide synthase, an enzyme promoting synthesis of more complex glycosphingolipids from glucosylceramide (Figure 1), which thereby inhibits synthesis of lactosylceramide from glucosylceramide.…”
Section: Sphingolipids Neutral Lipids and Ox-ldlmentioning
confidence: 95%